Prediksi Jumlah Retribusi Sampah Perbulan menggunakan Algoritma Decition Tree (C4.5) pada Kantor Dinas Lingkungan Hidup dan Kebersihan Kecamatan Selong Kabupaten Lombok Timur - Yupi Kuspandi Putra; Yeni Kurniatul Mahsun (Infotek: Jurnal Informatika dan Teknologi, 2018)
Along with the times and growing population growth, human needs are increasing. Every human being has diverse needs. Whatever humans need will produce something that must be discarded in the end and become waste. For the waste transportation services, the Environmental Service Office and the Hygiene Agency will collect fees from the relevant parties according to the specified amount. This fee collection is known as retribution. In order to help the office, a tool is needed to predict waste retribution revenue based on the daily retribution data. The algorithm model used is Decition Tree (C4.5) to get the rule in predicting the amount of monthly waste retribution at the Environmental and Hygiene Office of Selong District, East Lombok Regency. After three tests, all three showed high accuracy and AUC values. The most superior result is by using number of validation 3, with the accuracy value obtained is 96.51% and AUC value is 0.976% with a diagnosis level of excellent classification accuracy.DOI : 10.29408/jit.v1i1.893